ANALISIS PEMBIAYAAN MURABAHAH PADA LEMBAGA KEUANGAN MIKRO SYARIAH ( LKMS) ( STUDI KASUS PADA LKMS MM SEJAHTERA KOTA BENGKULU) - Amir Mukadar; Hesti Setiorini; Dharma Setiawan (Universitas Muhammadiyah Bengkulu, 2021)
ABSTRAK gone into effect of Code/Law No. 1 year 2013 about Micro Financial Institution ( LKM) hence since then standing many Micro Financial Institution both for operating by kovensional and or operate Moslem lawly , one of the Micro Financial Institution ( LKM) operating Moslem lawly that is Secure and prosperous LKMS MM which is have location in this Town Bengkulu Research aim to to know akad execution defrayal of murabahah in Secure and prosperous LKMS MM of Bengkulu and as according to Religious Advices Council Moslem law National MUI , this research is]research qualitative, that is in the form of an research procedure yielding descriptive data in the form of article or utterance and behavior which can be perceived from people itself subjek. Source of data become consideration in determination of data collecting method. Source of data consist of primary data and sekunder data. There is three data processing step qualitative, namely reduce data ( reduction data), presentation of data ( data displayed), and withdrawal of conclusion ( verification and drawing conclusion). Conclusion result of this research : Execution Defrayal of Murabahah at Secure and prosperous LKMS MM of Town Bengkulu not yet fully as according to Religious Advices Council Moslem law National MUI that is in the case of . In each application of defrayal [submitted/sent] murabahah by member / nasabah is not provided with member statement or promise / utk client buy produk from this LKMS matter of risk the happening of cancellation of murabahah by member/ client which later will harm LKMS party/ side in the case of policy of gift of margin cutting ( Muqashah) LKMS party/ side advise early this matter interfere in Religious advices DSN MUI which is policy ought to Keyword: LKMS, Akad Murabahah, Religious advices DSN MUI